Fabricating – Design – Research:: Examining the Integration of Digital Fabrication Technologies into the Architectural Curriculum - Boza, Luis Eduardo (ARCC Conference Repository, 2019)
This paper examines the roles that Digital Fabrication and Manufacturing technologies can have on the ability to Fabricate Design Research. In particular, it examines the ability of digital fabrication technologies to stimulate, initiate and integrate design research of various areas in the architectural curriculum. The paper explores the inherent relationships between fabricating, design and research and how one should understand their meanings in his/her own design process. As a primary case study, the paper will present student work from a course titled "Introduction to Techniques in Rapid Prototyping”, in which students were introduced to various digital fabrication tools and software. The student work demonstrates the interactive design process in which fabrication, design and research are interwoven in order to investigate new design methodologies based on new technologies.